HUKUM JUAL BELI AKUN MOBILE LEGEND BERDASARKAN METODE IJTIHAD DAN KAIDAH-KAIDAH PENGEMBANGAN HUKUM ISLAM - Kafa Nabil Birry (KASBANA, 2023)
The online game Mobile Legends is one of the most popular online-based games today. So that the users continue to grow and cause gamers who are engaged in the world of games to sell their Mobile Legends online game accounts because they have a sizable profit. The price offered varies greatly depending on the number of skins (changes in hero character) and other supporting attributes in the Mobile Legends game itself. The research method uses literature review or literature study which contains theories that are relevant to research problems. The results of this study indicate that the law of buying and selling online game accounts is reviewed on the urgency of Maqashid AsySyari'ah based on the considerations that Islam as a law based on God's revelation and intended for all its adherents will certainly follow social changes along with the times. The benefit of this online game account buying and selling system is included in the juz'iyyah maslahat category because it is of the muamalah type where the muamalah of buying and selling includes the benefit of both the seller and the buyer by using the divine benchmark in the use of online game accounts so that here we can understand the purpose or wisdom of Maqshid Asy-Shari'ah. Therefore, based on the review of maqasid As Syariah, the law of buying and selling game accounts is permissible. Keywords: Online games, Maqasid As-Syariah